Application of Interactive Technology in Multimedia-Based Learning Media Inspect History - Hasan (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The study investigates the impact of Inspect History, an interactive multimedia technology-based learning material, on student learning outcomes at SMA Negeri 9 Palu. The research aims to address students' limited interest and comprehension of standard history education. The study uses a quantitative, quasi-experimental design and involves class X students from two classes. Data analysis uses descriptive and inferential statistical methods. Results show that Inspect History significantly enhances student learning outcomes compared to traditional methods. Students show increased motivation and engagement during the educational process. The study concludes that Inspect History can effectively improve student learning outcomes in history at SMA Negeri 9 Palu and is expected to be utilized by history educators as a learning aid.